National Assessment of Achievement of Students Completing Grade 04 in Year 2006 - National Education Research and Evaluation Centre, University of Colombo (University of Colombo, 2006)
National Assessment of Achievement of Students Completing Grade 04 in Year 2006 ‘National Assessment of Achievement of Students Completing Grade 04 in Year 2006’ is a research study carried out by the National Education Research and Evaluation Centre (NEREC), Faculty of Education, University of Colombo. The objective of the research is to asses the achievement levels of students who have completed four years of schooling by 2006 and compare their achievement levels with the previous standards identified through the National Assessment conducted in 2003. The data collection for the study was done on 26th May 2007 throughout the country. A national sample of 10635 students representing all provinces, districts and zones was made use of. Province, gender, school type, medium of instruction and location (urban/rural) of school were the variables identified for purposes of data analysis. Other than the four tests Sinhala Language, Tamil Language, Mathematics and English Language administered in 2003 an additional test named Third International Mathematics and Science Study (TIMSS) Test was administered in this 2007 study. The achievement test data is analyzed on national and provincial basis, by individual subject and as a composite of three subjects tested excluding TIMSS, and by the variables identified. Statistical treatment of data has been adopted to facilitate meaningful data presentation and analysis. Findings: The all island achievement level as assessed using mean values, in Mathematics and First Language (Sinhala Language / Tamil Language) is high and in English language average. The mean scores in the three subjects are 70.96, 73.3, and 51.7, respectively. The percentages achieving mastery scoring 80 percent of total marks or above, 48.7, 56.5 and 19.6 respectively. All these values show that the average performance level of the students has improved at national level during the last four years. In sub-skills, the lowest student achievement is in writing in the Languages, as it was in the 2003 study. In Mathematics the sub skill of problem solving is poor in both studies. In level of achievement, there are differences in mean values by school type significant at the 95 percent level of confidence. Type 1AB schools have consistently achieved the highest and type 2 schools the lowest, in all three subjects. The achievement levels of 1C and type 3 schools lie in between. This pattern which was evident in 2003 has become a trend by 2007. The difference in achievement by gender, medium of instruction, location (urban/rural) of school and Province is significant at the 95 percent level of confidence. In achievement in all three subjects, by gender, girls, by medium of instruction, Sinhala medium, by location, urban, and by Province, Western Province, lead consistently. This was the same pattern that was found in the 2003 study too. The statistical analysis relating to TIMSS Mathematics test confirms that the performance of Sri Lankan students is average. As is evident in the other three subjects tested, the leading position of the Western province and comparatively poor achievement levels of Northern and Eastern provinces are evident. The improvement in learning achievement levels seen in 2007 has been a result of activities based on the dissemination programmes conducted by NEREC and the intervention programmes carried out by MoE and NIE with the support of the implementing agencies at provincial and zonal levels. The support of the funding agencies and various NGOs and the Educational Reform Programme too has contributed to the improvement in achievement levels. The emergence of the culture of using research findings for quality improvement at school level is noteworthy trend. Recommendations: To address the main areas of concern identified the following recommendations are made. 01. Improvements in curriculum designing 02. Special programmes on school development 03. Introduction of an alternative assessment approach at school level 04. Implementation of a bench marking programme 05. Implementation of a remedial intervention programme 06. Capacity building activities